A Modified Surgical Technique to Prevent Parastomal Hernia - Fan, Zhuolin; Guan, Weiyu; Zhang, Tao; Zhang, Dewei (Frontiers in Surgery, 2022)
Extraperitoneal colostomy is not sufficiently effective to prevent parastomal hernias. On the basis of anatomic structures and mechanical principles, we modified this surgical technique by preserving the integrity of the posterior rectus abdominis sheath to prevent parastomal hernia, and we applied it clinically.